2009
DOI: 10.1111/j.1468-3083.2008.02944.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of short- and long-pulsed mode of electro-optical synergy technology for photoepilation: A retrospective study with short- and long-term follow-up

Abstract: Two passes with this combined-energy system are an effective treatment option for the removal of thin, thick, fair and dark hair; however, the system has no significant advantages over other available methods of photoepilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Similar results were reported in a study of 87 patients which showed mean hair reductions of 43% for black hair, 49% for brown hair, and 35% for blonde hair (p < 0.05 all groups) [13]. Conversely, one study demonstrated no significant difference in hair clearance efficacy between fair-and dark-colored hair (p = 0.872) [14]. Sadick et al [18] specifically studied lighter colored hair removal and reported greater efficacy of blonde facial hair removal compared to white facial hair (52% vs. 44%) after four treatments in 36 patients.…”
Section: Hair Reductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were reported in a study of 87 patients which showed mean hair reductions of 43% for black hair, 49% for brown hair, and 35% for blonde hair (p < 0.05 all groups) [13]. Conversely, one study demonstrated no significant difference in hair clearance efficacy between fair-and dark-colored hair (p = 0.872) [14]. Sadick et al [18] specifically studied lighter colored hair removal and reported greater efficacy of blonde facial hair removal compared to white facial hair (52% vs. 44%) after four treatments in 36 patients.…”
Section: Hair Reductionsupporting
confidence: 84%
“…RF appeared to be well tolerated by patients of all Fitzpatrick skin types in the hair removal studies, with no serious adverse events being reported. The most commonly reported adverse events were minor, including transient erythema, edema, hyperpigmentation, and mild treatment-associated pain [10,13,14,17,18]. A total of 7 patients treated with mRF across the three trichiasis studies developed eyelid notching [6,8,9].…”
Section: Hair Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An innovative concept was presented by Karsai et al [21]. In a retrospective study, they assessed the short-and longterm effectiveness of an electro-optical synergy device (IPL (l em ¼ 680-980 nm)/bipolar radiofrequency-RF) for hair removal in patients (n ¼ 24) with unwanted facial hair.…”
Section: Hair Removalmentioning
confidence: 99%